Master key to riches - "Hill, Napoleon" (London, 2004)
Based on Andrew Carnegie's famous formula for money-making, Master key to Riches has been revised and updated for the 21st century. As well as explaining the practical philosophy for success, in this inspiring book Napoleon Hill describes the key that will convert all your past failures into priceless assets and lead you to the attainment of the twelve great riches.
Keywords: Success